Jamur Kayu Sebagai Inspirasi Gaun Pengantin - Cindi Khairani; Desra Imelda (Penerbit dan Percetakan, CV. Picmotiv, 2025)
A wedding gown inspired by wood fungus using a ball gown cut is designed with a luxurious and elegant shape. The wedding gown is included in the haute couture fashion group or exclusive fashion, namely high-level fashion. Wood mushrooms is visualized on wedding dresses by realizing wave shapes and gradient colors. The choice of colors is directly inspired by the wood mushrooms, namely brown, coffee, cedar, khaki, beige. The materials used t create this work are bridal satin fabric, thousand-payet squins fabric, organza, and Riau Malay songket woven fabric as a combination fabric. The creation method begins with preparation, namely searching for literature or references related to the idea of creating the embodiment of the work to be created. This work uses the 2024/2025 tend forecasting theme of ergo tech which applies designs using new materials, namely using slippery and glossy materials. The techniques used in this work are flounce and squins applications with a haute couture approach.